1996
DOI: 10.1016/s0266-7681(96)80175-6
|View full text |Cite
|
Sign up to set email alerts
|

Pronator Quadratus Revisited

Abstract: The pronator quadratus muscle has been neglected to a great extent in the anatomical and functional literature. This study confirms the consistent presence of two distinct heads to the muscle, and defines the gross and microscopic anatomy. The functional significance of these heads has been studied using in vitro and in vivo techniques to demonstrate that the superficial head is the prime mover in forearm pronation, and that the deep head is a dynamic stabilizer of the distal radioulnar joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 10 publications
4
76
0
8
Order By: Relevance
“…This finding is somewhat corroborated by Murray and coworkers, 18 who found that the pronator teres moment arm decreased in the fully pronated position. As well, the pronator quadratus muscle has previously been considered a joint stabilizer rather than an agonist for pronation, 19 which also supports the observation that it does not contribute to the pronation torque. This leads to the obvious question of which muscles are instigating the pronation moment required to maintain this position.…”
Section: Discussionsupporting
confidence: 70%
“…This finding is somewhat corroborated by Murray and coworkers, 18 who found that the pronator teres moment arm decreased in the fully pronated position. As well, the pronator quadratus muscle has previously been considered a joint stabilizer rather than an agonist for pronation, 19 which also supports the observation that it does not contribute to the pronation torque. This leads to the obvious question of which muscles are instigating the pronation moment required to maintain this position.…”
Section: Discussionsupporting
confidence: 70%
“…We have evaluated the results with reference to radiological union and clinical and functional outcome at the end of six months. Deep head of pronator quadratus acts as a dynamic stabilizer of the distal radio-ulnar joint [12,13] . It contributes 21% of the pronator strength of wrist joint [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Although PQ was described in anatomic texts more than 400 years ago, it did not gain popularity until the biomechanics of the distal radio-ulnar joint became clear [2]. In 1976, Johnson et al [1] reported two distinct heads of PQ.…”
Section: Discussionmentioning
confidence: 99%
“…While the superficial layer of PQ acts in coordination with the pronator teres and serves for forearm pronation, deep layer inserts joint capsule and take part in radio-ulnar joint stabilization [1][2][3]. In addition, both heads of the pronator quadratus also play a role in grip strength [4].…”
Section: Introductionmentioning
confidence: 99%